1995
DOI: 10.1111/j.1600-051x.1995.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament tissue reactions to trauma and gingival inflammation

Abstract: The aims of the present study were to analyze (i) which tissue changes may occur in the zone of co-destruction to better understand why trauma from occlusion may induce additional attachment loss, and (ii) whether changes occur in the periodontal ligament tissue when an inflammatory lesion (ICT) approaches the periodontal ligament space. 16, 1-year-old beagle dogs, were selected and divided into 2 groups, group A and group B, consisting of 6 and 10 dogs, respectively. In group A, on day 0, a bucco-lingual jigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“… and Biancu et al . observed a reduced amount of supra‐alveolar collagen in a model of jiggling traumatic occlusion, and they suggested that the alterations of the supra‐alveolar tissue could influence the route of spread of inflammation. In the present study, we showed that collagen fibers oriented from the root surface toward the alveolar bone crest decreased or disappeared.…”
Section: Discussionmentioning
confidence: 99%
“… and Biancu et al . observed a reduced amount of supra‐alveolar collagen in a model of jiggling traumatic occlusion, and they suggested that the alterations of the supra‐alveolar tissue could influence the route of spread of inflammation. In the present study, we showed that collagen fibers oriented from the root surface toward the alveolar bone crest decreased or disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study shows that bone resorption occurs along the full extent of the tooth root, as well as in the centre of the alveolar septum. It also increases the activity of osteoclasts [23][24][25] involved in inflammatory bone resorption, 51 maintaining the latter as an active process until 21 days post-trauma, thus delaying the recovery of the PDL width following subluxation. [47][48][49] Thus, subluxation may induce bone resorption because of its capacity to provoke TO through the minor extrusion of the tooth caused by the trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Subluxation of teeth with incomplete root development may lead to an increase in inflammatory resorption (1.7%). 21,22 In addition, TO can cause morpho-functional alterations such as disorientation and decrease in collagen fibres, 23,24 change in the alignment of periodontal fibres, 25,26 an increase in the number of fibroblasts, 23 increased osteoclast activity, [23][24][25] venous thrombosis 23 and PDL cell necrosis. 21,22 In addition, TO can cause morpho-functional alterations such as disorientation and decrease in collagen fibres, 23,24 change in the alignment of periodontal fibres, 25,26 an increase in the number of fibroblasts, 23 increased osteoclast activity, [23][24][25] venous thrombosis 23 and PDL cell necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Given that biological complications cause inflammation and the loss of tissue and bone in the surrounding implant, and increase the risk of implant failure, these complications need to be managed carefully. Conversely, the disconnection and reconnection are more convenient for 1-IR, and examining and ensuring the hygiene of the prosthesis are easier than for the splinted implant restoration 4142…”
Section: Discussionmentioning
confidence: 99%